2015
DOI: 10.1016/j.foodchem.2015.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk type and processing on iodine concentration of organic and conventional winter milk at retail: Implications for nutrition

Abstract: Milk is the largest source of iodine in UK diets and an earlier study showed that organic summer milk had significantly lower iodine concentration than conventional milk. There are no comparable studies with winter milk or the effect of milk fat class or heat processing method. Two retail studies with winter milk are reported. Study 1 showed no effect of fat class but organic milk was 32.2% lower in iodine than conventional milk (404 vs. 595 μg/L; P<0.001). Study 2 found no difference between conventional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 16 publications
(24 reference statements)
7
50
2
1
Order By: Relevance
“…A higher level of iodine in skimmed milk was found in a study conducted in Spain (Soriguer et al, 2011), but a study from United Kingdom (Payling et al, 2015) and another study from Germany (Kohler et al, 2012) did not find significant differences in iodine concentration between milk types.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A higher level of iodine in skimmed milk was found in a study conducted in Spain (Soriguer et al, 2011), but a study from United Kingdom (Payling et al, 2015) and another study from Germany (Kohler et al, 2012) did not find significant differences in iodine concentration between milk types.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, organic milk has been shown to contain less iodine (Rasmussen et al, 2000;Dahl et al, 2003;Bath et al, 2012;Kohler et al, 2012;Payling et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning iodine contents, it has been observed that in organic milk they are present in concentrations of about 30-40% lower than in conventional milk [34,35]. In this regard, it is worth mentioning the study of Rey-Crespo et al [36] on essential trace elements and some heavy metal residues in organic and conventional milk carried out in Spain, 2013.…”
Section: Organic Vs Conventional Milk: Focus On Fat Fraction and Minmentioning
confidence: 94%
“…; Payling et al . ) and UHT milk (Payling et al . ) (reviewed in Chambers ); however, both can still be considered as rich sources of iodine according to the European Commission definition (EC ).…”
Section: Dietary Sources Of Iodine Including Milkmentioning
confidence: 99%